Lying in the plural: a proposal for classifying fake news - Silveira, Fábio Alves [UNESP] (My University, 2023)
The phenomenon of misinformation in the era of social networks has the spread of fake news as one of its pillars. The objective of this article is to identify patterns in the production of fake news released during the Covid-19 pandemic to justify the denialist policies adopted by the Brazilian government. The corpus consisted of 142 articles checked by the agencies Lupa e Fato ou Fake between May and October 2021. The exploratory research, of a qualitative and quantitative nature, used content analysis and deductive method. Two categories of fake news were identified: invention and adulteration; the latter being divided into four subcategories: distortion, decontextualization, fraud, false symmetry. Although 50% of the fake news was forged by primary invention processes, the analysis identifies that the other half was made up of distorted content that indicates a complex structure for financing production.
Mentir no plural: uma proposta de classificação das fake news
Keywords: fake news; journalism; pandemic; politics; public debate